Real-world retrospective study of immune checkpoint inhibitors in combination with radiotherapy or chemoradiotherapy as a bladder-sparing treatment strategy for muscle-invasive bladder urothelial cancer - Xu, Chao; Zou, Wen; Zhang, Lei; Xu, Ran; Li, Yuan; Feng, Yeqian; Zhao, Runtian; Wang, Yinhuai; Liu, Xianling; Wang, Jingjing (Frontiers in Immunology, 2023)
ABSTRACT Background: Recent developments in MIBC treatment suggest good efficacy of bladder sparing treatment combined with immune checkpoint inhibitor. However, there is no standard treatment mode. A retrospective analysis was conducted to reveal the efficacy and safety of PD-1 inhibitor in combination with radiotherapy or chemoradiotherapy. Methods： We retrospectively analyzed 25 patients with MIBC T2-T3N0M0 disease who were unfit or unwilling to undergo RC. These patients underwent the maximum TURBT followed by PD-1 inhibitor (Tislelizumab or Toripalimab) in combination with radiotherapy or chemoradiotherapy (gemcitabine plus cisplatin) between April 2020 and May 2022. The primary outcome was clinical complete response (cCR) rate. The secondary outcomes were disease free survival (DFS) and overall survival (OS). Results： Revised: Of 25 patients, 22 were T2 (88%), while 3 were T3 (12%). The median age is 65 years (51–80). Twenty-one patients had programmed cell death ligand 1 (PD-L1) combined positive score (CPS) of 1 or more, and 4 patients had CPS<1 or unknown. Sixteen patients received chemoradiotherapy. Tislelizumab and Toripalimab were administered to 19 and 6 patients, respectively. The median number of cycles of immunotherapy was 8. Twenty-three patients (92%) achieved cCR. Following a median of 13 months of follow-up (range, 5-34 months), 1-year DFS and OS rate were 92% and 96%, respectively. In the univariate analysis, T stage significantly influenced OS and ORR, and efficacy evaluation significantly influenced OS, DFS, and ORR. The expression of PD-L1 and chemotherapy had no effect on prognosis. In the multivariate analysis, no independent prognostic factors were found. Grade 3 or 4 adverse events (AE) were reported in 35.7% patients. Conclusions： Bladder sparing therapy with PD-1 inhibitor in combination with radiotherapy or chemoradiotherapy is feasible, safe, and highly effective for patients who were unfit or unwilling to undergo RC.